COMPONENT ANALYSIS OF CREATIVE THINKING ABILITY ON STATIC FLUID MATERIALS, TEMPERATURE, HEAT, AND OPTICAL TOOLS IN SMA BOOK IN CLASS XI IN WEST SUMATERA - Septi Putri Dewi; - Hufri; - Hidayati; Silvi Yulia Sari; Fanny Rahmatina Rahim (PILLAR OF PHYSICS EDUCATION, 2022)
Higher thinking skills must be possessed by students in facing 21st century education. Creative thinking skills are needed in various ways, especially in learning to improve student learning outcomes in class. So that text books are needed as a support for the learning process. For this reason, it is necessary to pay attention to whether the textbooks used are in accordance with the demands of the current 2013 curriculum. One of the curricula in the 2013 curriculum is the use of texts that can facilitate students' creative thinking skills. So it is necessary to analyze physics learning textbooks for class XI semester 2 on static fluid, temperature and heat materials as well as optical devices to find out whether the presentation of physics textbooks for class XI facilitates creative thinking skills. The population in this study were all textbooks for physics class XI published in Indonesia and used in West Sumatra. The samples used in this study were MK-ER textbooks and MR-TS textbooks. The results of the analysis show that the MR-TS physics textbook is a physics textbook with the highest level of availability of creative thinking indicators with a percentage of 38.69% in the less available category. While the MK-ER physical textbook has the lowest level of availability of creative thinking indicators with 37.68% results being in the less available category. This shows that the MR-TS physics textbook and MK-ER physics textbook have not been perfect in facilitating students creative thinking skills.